Lipid Metabolism and HCV Infection - Targett-Adams, Paul (Molecular Diversity Preservation International (MDPI), 2010)
Chronic infection by hepatitis C virus (HCV) can lead to severe liver disease and is a global healthcare problem. The liver is highly metabolically active and one of its key functions is to control the balance of lipid throughout the body. A number of pathologies have been linked to the impact of HCV infection on liver metabolism. However, there is also growing evidence that hepatic metabolic processes contribute to the HCV life cycle. This review summarizes the relationship between lipid metabolism and key stages in the production of infectious HCV.